2009
DOI: 10.1096/fasebj.23.1_supplement.688.6
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cytochrome P450 1A2 and 3A4 by Morinda citrifolia (noni), Euterpe oleracea (acai), Lycium barbarum (goji) and Garcinia mangostana (mangosteen)

Abstract: The use of complementary and alternative medicine (CAM) including herbal products, for health maintenance and treatment of chronic diseases is continuously rising in the United States. Although considered safe due to their "natural" origin, herbal products are prone to herb‐drug interactions. Cytochrome (CYP) P450 enzymes are responsible for metabolizing xenobiotics including herbal products. The aim of our study was to investigate the effects of Morinda citrifolia (noni), Euterpe oleracea (açai), Lycium barba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Extracts of noni have been shown to modulate the metabolic activities of multiple CYP isoforms. [ 120 , 121 ]. In a published report, Kang et al reported the case of a patient whose epilepsy has been managed with phenytoin for over 10 years without major side effects [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Extracts of noni have been shown to modulate the metabolic activities of multiple CYP isoforms. [ 120 , 121 ]. In a published report, Kang et al reported the case of a patient whose epilepsy has been managed with phenytoin for over 10 years without major side effects [ 33 ].…”
Section: Resultsmentioning
confidence: 99%